Impact of Supply Chain Traceability on Risk Management and Resilience - Selvaraj, Manikandan; Raman , Rohit (International Journal of Supply Chain and Logistics, 2025)
Purpose: To investigate how traceability can enhance risk awareness, optimize risk management strategies, and foster resilient supply chain systems in the face of global economic volatility and interconnectedness. Methodology: An extensive literature review was conducted to examine the relationship between traceability and risk awareness in supply chain management. Findings: The study revealed that improved traceability significantly enhances supply chain visibility, enabling managers to identify potential vulnerabilities more effectively. Technologies such as AI and machine learning play a crucial role in facilitating timely response and resolution of issues before they escalate. The research also highlighted the importance of leveraging technology to improve traceability, even for small businesses, as it contributes to their competitiveness. Unique contribution to theory, practice and policy: This study emphasizes the critical role of traceability as an effective tool for risk management and building resilient supply chain systems. It underscores the importance of technological adoption in enhancing traceability across businesses of all sizes, contributing to both theoretical understanding and practical applications in supply chain management.